Pelatihan Pembuatan Kerajinan Tangan Dari Barang Bekas Pada Anak Di KP. Golat Desa Pangkalan Kab. Pandeglang - Shindi Aulia; Nuraeni Nuraeni; Rifki AM; Dede Imtihanudin; Ratna Dewi (Institut Nalanda, 2023)
Garbage is one of the big problems in Indonesia from organic and non-organic waste, plastic waste as an example of non-organic waste which takes a long time to decompose even the use of plastic waste in Indonesia has been limited to emergency besides the fiber power from waste recycling and management activities Waste is still very low with waste management activities, which is a creative idea and an effective solution for waste management in Indonesia. With the training on handicraft arts from used goods conducted by KKN-T students from the PGSD Study Program to children in kp. It is hoped that the village of Base Village of Pandeglang Regency will have children in KP. golat is more skilled, active, and able to show his creativity and understand the use of used goods around him. The children together make works with the direction of the teacher and according to the examples that have been prepared beforehand. The targets given [the teaching] are children aged 7-10 years whose works are in the form of piggy banks and flower pots.